DARI MITOS KE MEMORI: TRADISI LISAN SEBAGAI MEDIA TRANSMISI PENGETAHUAN VULKANIK DI GUNUNG KELUD - Rahmad Agus Majid; A. Zahid (Saka Bahasa: Jurnal Sastra, Bahasa, Pendidikan, dan Budaya, 2026)
Volcanic events are rarely understood solely as geophysical phenomena; instead, they are articulated through mythological narratives that encode collective ecological experiences. This study examines how oral tradition functions as a medium for transmitting volcanic knowledge among communities living on the slopes of Mount Kelud, East Java, Indonesia. Utilizing a descriptive qualitative approach, in-depth interviews were conducted with community elders and local knowledge keepers selected through purposive sampling. The findings reveal three interconnected dynamics: oral narratives contain sophisticated pre-scientific indicators of volcanic activity sulfur odors as early warning proxies, changes in animal behavior as ecological signals, and sacred spatial prohibitions as risk zone demarcations; traumatic eruption experiences are continuously reconstructed into symbolic narratives through social interaction, forming a living collective memory that serves as cross-generational risk education; and this transmission chain is becoming increasingly fragile under the pressures of digital culture and the epistemological authority of modern volcanology. This study argues that oral tradition constitutes a legitimate epistemological system that complements, rather than refutes, scientific hazard management.   Peristiwa vulkanik jarang dipahami semata-mata sebagai fenomena geofisika, ia diartikulasikan melalui narasi mitologis yang mengodekan pengalaman ekologis kolektif. Penelitian ini mengkaji bagaimana tradisi lisan berfungsi sebagai medium transmisi pengetahuan vulkanik pada komunitas yang tinggal di lereng Gunung Kelud, Jawa Timur, Indonesia. Menggunakan pendekatan kualitatif deskriptif, wawancara mendalam dengan sesepuh komunitas dan penjaga pengetahuan lokal yang dipilih melalui purposive sampling. Temuan menunjukkan tiga dinamika yang saling terkait narasi lisan mengandung indikator pra-ilmiah yang canggih tentang aktivitas vulkanik bau belerang sebagai proksi peringatan dini, perubahan perilaku hewan sebagai sinyal ekologis, dan larangan spasial sakral sebagai demarkasi zona risiko, pengalaman traumatik erupsi terus direkonstruksi menjadi narasi simbolik melalui interaksi sosial, membentuk memori kolektif yang hidup dan berfungsi sebagai pendidikan risiko lintas generasi dan rantai transmisi ini semakin rapuh di bawah tekanan budaya digital dan otoritas epistemologis vulkanologi modern. Penelitian ini berargumen bahwa tradisi lisan merupakan sistem epistemologis yang sah yang melengkapi, bukan menyangkal, manajemen bahaya ilmiah.